Optimization of insulation thickness of walls and roofs using energy, exergy, economic and environmental analyses - Ucar, Aynur (Univ Malaysia Pahang, 2024)
- Buildings play an important role in consumption of energy and carbon dioxide emissions all over the world. The optimum thickness of each insulation material of wall and roof of residential buildings depending on energy, environment, economy and exergy w
Keywords: Optimum insulation; Thickness; 4E analysis; Optimization model; CO2 emissions; Exergy